2001
DOI: 10.1016/s1010-7940(01)00611-x
|View full text |Cite
|
Sign up to set email alerts
|

Recurrences following videothoracoscopic treatment of primary spontaneous pneumothorax: the role of redo-videothoracoscopy

Abstract: In the light of our initial experience, redo-VATS seems to be a promising tool for the surgical therapy of recurrences following VATS treatment of primary spontaneous pneumothorax.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 9 publications
1
28
1
2
Order By: Relevance
“…The safety of talc has been further established with the observation that talc poudrage does not alter lung function [117,118,125,137]. Following talc pleurodesis, VATS has been shown to be feasible [138,139]; however, it is the opinion of some Task Force members that it is more technically demanding [106]. Talc poudrage is very cost-effective and, in fact, more economical than a conservative approach using only chest tube drainage [140].…”
Section: Indicationsmentioning
confidence: 99%
“…The safety of talc has been further established with the observation that talc poudrage does not alter lung function [117,118,125,137]. Following talc pleurodesis, VATS has been shown to be feasible [138,139]; however, it is the opinion of some Task Force members that it is more technically demanding [106]. Talc poudrage is very cost-effective and, in fact, more economical than a conservative approach using only chest tube drainage [140].…”
Section: Indicationsmentioning
confidence: 99%
“…The bullae/blebs in patients with PSP can be managed through VATS by stapling and resection, no-knife stapling, suturing, or endo-loop ligation (Liu et al, 1999;Cardillo et al, 2001;Luh and Liu, 2006). Pleurodesis is usually required in addition to bullae/ blebectomy for surgical management of patients with PSP.…”
Section: Surgical Management Of Pspmentioning
confidence: 99%
“…Some authors have suggested that a complete pleurolysis should be performed to search for bullae missed at first operation [6]. In the largest series of redo VATS after such recurrences, Cardillo et al operated on 19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Complete adhesiolysis was performed in all cases. But bullae were found and stapled in only nine cases [6]. However, this method entails the risk of injuring the lung during adhesiolysis.…”
Section: Discussionmentioning
confidence: 99%